The Effect of Carica pubescens Seeds Ethanol Extract on Lymphocyte Count and Paw Edema in Male White Swiss Webster Mice - Luhurningtyas, Fania Putri; Novitasari, Evi (Universitas Pakuan, 2024)
Inflammation is a natural tissue response to infection in the body. The potential anti-inflammatory effect of secondary metabolites in carica seeds has been overlooked. This study aimed to investigate and develop the anti-inflammatory activity of the ethanolic extract of carica seeds (Carica pubescens) against foot edema and lymphocyte count in male white mice. Bioactive carica seeds were extracted using the maceration method with 70 % ethanol solvent. The identification of secondary metabolites was conducted using the thin-layer chromatography method. Treatments were administered to six groups: the negative control group (sick), solvent control, positive control with Diclofenac Sodium, and three doses of the ethanol extract of carica seeds (cS) at 100, 200, and 400 mg/kg body weight (BW). Edema was induced using intraplantar 1 % carrageenan on the soles of mice, and lymphocyte count was determined by blood sampling from the lateral tail vein using a hematology analyzer. Carica seeds doses of 200 mg/kg BW and 400 mg/kg BW demonstrated anti-inflammatory activity comparable to the positive control Diclofenac Sodium (p 0.05). Variations in CS doses influenced the lymphocyte count at the 3rd and 6th hours. In conclusion, the ethanolic extract of carica seeds exhibits anti-inflammatory effects in male white mice induced by 1 % carrageenan, reducing edema thickness and affecting leukocyte count.